Implementation of the Card Sort Method in Improving the Learning of Aqidah and Akhlak through the Demonstration Method for MIS Nurul Iman Students - Hanum, Yusma (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the application of the Card Sort method in improving learning of Akidah Akhlak, especially on the material of Kalimat Tayyibah Ta'awudz, through the demonstration method on grade 2 students of MIS Nurul Iman. The background of this study is the low understanding of students on the material of Kalimat Tayyibah Ta'awudz due to less interactive learning methods. The Card Sort method is applied to increase student involvement in learning and help them understand and memorize the material more effectively. This study uses the Classroom Action Research (CAR) method with a qualitative and quantitative approach. The subjects of the study were grade 2 students of MIS Nurul Iman. Data collection techniques include observation, interviews, learning outcome tests, and documentation. The data obtained were analyzed descriptively by comparing the results before and after the application of the Card Sort method. The results showed that the Card Sort method was able to significantly improve students' understanding of the material of Kalimat Tayyibah Ta'awudz. Students were more active and enthusiastic in learning, and showed an increase in learning outcomes. In addition, this method also helps teachers in creating a more interesting and effective learning atmosphere. The obstacles found in the implementation of this method can be overcome with careful planning and intensive guidance to students. The results of the analysis showed a significant increase in student engagement and their learning outcomes after the implementation of this method. Thus, the Card Sort method has proven effective in improving the learning of Akidah Akhlak on the material of Kalimat Tayyibah Ta'awudz. It is recommended for educators to adopt this method as an alternative learning strategy that is more interactive and innovative. The implementation of this method can also be combined with other learning strategies to improve the effectiveness of teaching.